Radiofrequency Ablation for Chronic Hip Pain: A Comprehensive, Narrative Review. (23rd July 2021) - Cheney, Cole W; Ahmadian, Amir; Brennick, Caroline; Zheng, Patricia; Mattie, Ryan; McCormick, Zachary L; Nagpal, Ameet
Abstract: Chronic hip pain can be treated with physical therapy, oral medications, injections, and, definitively, total hip arthroplasty. Enough patients have contraindications to and refractory pain even after total hip arthroplasty, that there is a need to develop alternative managements for this disabling condition. This article examines the state of hip radiofrequency ablation literature including relevant anatomy, patient selection, and treatment outcomes.